The Effect of Work Motivation, Work Discipline and Supervision on Employee Performance at PT Cahaya Marine Indonesia in Batam - Imelda Mite; Feliks Dabur; Laurensius Dihe Sanga (Tractare: Jurnal Ekonomi-Manajemen, 2026)
ABSTRACT This study aims to determine the influence of work motivation, work discipline, and supervision, both partially and simultaneously, on the performance of employees at PT Cahaya Marine Indonesia in Batam City. The research was conducted using a quantitative method with a total population of 90 respondents. The sampling technique employed was the saturated sampling method, in which the entire population was used as the sample. Data were collected through questionnaires distributed via Google Forms. Data analysis was carried out using SPSS version 26. The results of the study indicate that the work motivation variable has a t-value of 0.194 < t-table value of 1.662 with a significance level of 0.846 > 0.05, thus H₀ is accepted and Hₐ is rejected. The work discipline variable has a t-value of 2.131 > t-table value of 1.662 with a significance level of 0.036 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. The supervision variable has a t-value of 4.140 > t-table value of 1.662 with a significance level of 0.000 < 0.05, meaning that H₀ is rejected and Hₐ is accepted. Furthermore, the three variables—work motivation, work discipline, and supervision—simultaneously have an F-value of 29.967 > F-table value of 2.71 and a significance level of 0.000 < 0.05. This indicates that work motivation, work discipline, and supervision together have a positive and significant effect on employee performance at PT Cahaya Marine Indonesia in Batam City.